Pengaruh Kompetensi Aparatur Desa, Sistem Pengendalian Internal Dan Penerapan Budaya Tri Hita Karana Terhadap Kecenderungan Kecurangan Dana Desa Se-Kecamatan Banjar Buleleng - Mitha, Dewa Ayu Putu Pradnya; Sumadi, Ni Komang; Wati, Ni Wayan Alit Erlina (UNHI Press, 2025)
Village Fund Management, in accordance with the mandate of Law Number 6 of 2014, requires evaluation to ensure that there are no deviations in the use of APBN funds distributed annually as a source of village income. This evaluation also aims to optimally integrate all budget allocation activities from the government to the village (Directorate General of Fiscal Balance, 2023). The purpose of the study was to determine the level of Village Apparatus Competence, Internal Control System, Implementation of Tri Hita Karana on the Tendency of Village Fund Fraud in Banjar Buleleng District. The data in this study came from primary data in the form of questionnaires. The subjects in the study were 17 Village Offices in Banjar District, Buleleng Regency with a total of 153 Village Office employees. The results of the analysis showed that Village Apparatus Competence, Internal Control System, and Implementation of Tri Hita Karana all had a negative effect on the Tendency of Village Fund Fraud in Banjar Buleleng District, which means that the higher the three factors, the lower the tendency for fraud.